Soil fertility and leaf nutrient status of litchi orchard sites - Zannat, Tasnim; Meem, Farhana Firoz; Promi, Rubaiat Sharmin; Poppy, Umme Qulsum; Rahman, MK (Dhaka University Journal of Biological Sciences, 2021)
Twelve soil and twelve leaf samples were collected from twelve litchi (Litchi chinensis Sonn.) orchards from different locations of Dinajpur to evaluate some physico-chemical properties and nutrient status of soil, and concentration of nutrients in litchi leaf. The pH of the soil varied from very strong acidic to medium acidic (4.8 - 5.7), organic matter content varied from 0.84 - 1.88%, EC varied from 302.4 - 310.2 μS/cm. The dominant soil textural class was clay loam. The average particle density was 2.49g/cm3. Total N, P, K and S in soils were 0.053 - 0.180%, 0.02 - 0.07%, 0.046 - 0.370 meq/100 g, and 0.015 - 0.028%, respectively. Available N, P, K, S, Zn, Fe, Mn and B in soils 30.40 - 57.8 mg/kg, 10.53 - 14.33 mg/kg, 0.03 - 0.32 meq/100 g, 20.03-34.80 mg/kg, 0.68-1.50 μg/g, 31.8 - 41.5 μg/g, 6.75 - 7.39 μg/g and 0.25-0.51 μg/g, respectively. The concentration of total N, P, K, S, Zn and Mn in the leaf were 1.74 - 2.20%, 0.11 - 0.188%, 0.104- 0.198%, 0.129 - 0.430%, 12 - 14 μg/g and 30 - 74 μg/g, respectively. The overall results indicated that the fertility status of the soils under the litchi plantation in the Dinajpur area are medium fertile. So, farmers could be advised to grow litchi plants after applying amendments to the soils to improve the physico-chemical properties in the Dinajpur area of Bangladesh. Dhaka Univ. J. Biol. Sci. 30(2): 141-149, 2021 (July)